Associations between patterns of participation in community activities and social support, self-efficacy, self-rated health among community-dwelling older adults. (January 2023) - Nagao-Sato, Sayaka; Akamatsu, Rie; Karasawa, Miki; Tamaura, Yuki; Fujiwara, Keiko; Nishimura, Kazuhiro; Sakai, Masashi
Abstract: Certain types of community-based social activities improve the health issues of older adults; however, the present patterns of participation in community activities remain unknown. This study aims 1) to identify community-dwelling older adults' patterns of participation in community-based activities and 2) to evaluate the relationships between social support, self-efficacy, self-rated health, and the patterns of participation in community activities. This cross-sectional study used data collected from 146 older adults aged ≥65 years who participated in community events in Japan in 2018. Cluster analysis was used to identify subjects' patterns of participation in community activities. In the multinomial logistic regression model, the participation pattern (dependent variable), and social support and self-efficacy (independent variables), were included, adjusting for age, sex, and years of residency. Three participation pattern clusters were identified: diverse activities (58%), municipal events (30%), and senior citizen club (12%). The proportion of participants reported themselves healthy were 93%, 88%, and 78% for diverse activities, municipal events, and senior citizen club clusters, respectively. Compared to those in the senior citizen club cluster, older adults in the diverse activities cluster were more likely to have self-efficacy (adjusted odds ratio (a OR ): 1.19, p  = .041) and social support (a OR : 2.35, p  = .018), while participants in the municipal events cluster were associated with only social support (a OR : 3.29, p  = .022). Increasing social support and self-efficacy may promote seniors' participation in diverse community activities, which would be beneficial for their healthy aging. Further studies are needed to evaluate the causal relationships.